ANALYSIS OF WORK MOTIVATION AND WORK DISCIPLINE TOWARDS WORK SATISFACTION AND ITS IMPLICATIONS ON EMPLOYEE PERFORMANCE (SURVEY STUDY AT BHAYANGKARA HOSPITAL LEVEL III MANADO) - Lopulalan, Jopie Julius; Yuliaty, Farida; Rasyid, Renaldi Prasetya Nagar; Kosasih, Kosasih; Rahmiyati, Ayu Laili (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Work motivation plays an important role for hospital employees because it can be a motivator for individuals to carry out an activity optimally. This is also related to work discipline and job satisfaction. So that employee performance needs to be measured to determine the ability of employees to support the hospital institution's strategy in improving services. This study aims to analyze the work motivation, work discipline, job satisfaction and employee performance at Bhayangkara Hospital Level III Manado. This study uses a quantitative approach. The sample in this study amounted to 78 respondents. Data analysis used is descriptive analysis and verification analysis using path analysis. The results of the descriptive analysis study on work motivation, work discipline, job satisfaction and employee performance with a good assessment, there are still some that need to be improved. While the results of the verification study, the path analysis model shows the value of the path coefficient of the work motivation variable on employee performance is positive and the value of the indirect influence path coefficient is greater than the direct influence (24.2%> 8.8%), likewise the work discipline variable on employee performance is positive and the value of the indirect influence coefficient is greater than the direct influence (48.1%> 34.3%) meaning that the job satisfaction variable as an intervening variable is able to mediate the work motivation variable and the work discipline variable on the employee performance variable.